Pelaksanaan Pendampingan Perkawinan Beda Agama Pasca Sema No 2 Tahun 2023 di LSM Percik Salatiga - Faiza Rachmadani; Anjar Sri Ciptorukmi Nugraheni (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
This research uses an empirical research approach by examining primary data. Interfaith marriage is a physical and spiritual bond between a man and a woman with the aim of forming a happy and eternal family based on the Almighty God, but the man and woman are of different religions. This research was conducted because the various regulations on Interfaith Marriage which have multiple interpretations are interesting to study their implementation in society. The publication of SEMA No.2 of 2023 concerning the prohibition on judges granting requests for registration of interfaith marriages is interesting to study its implementation in society, especially in Salatiga. The results of this research are assistance for interfaith marriages at the Percik Salatiga NGO and registration of interfaith marriages at the Salatiga Disdukcapil post SEMA No. 2 of 2023 is still ongoing.